Bibliometric Analysis of Rice Husk Biomass Potential as an Environmentally Friendly Alternative Fuel - Sabikah Nur Naylah; Diki Ramadhani; Muhammad Andhika Ramadhan; Rika Romatona; Muhammad Ashbar As-Silmy; Erza Arkan Zharif (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2026)
The increasing global energy demand and environmental concerns have intensified the search for sustainable alternative fuels. Rice husk, an abundant agricultural by-product in rice-producing countries, has attracted growing attention as a promising biomass resource. However, previous studies have mainly focused on technical conversion processes, while limited research has systematically examined publication trends and thematic developments in this field. Therefore, this study aims to analyze global research trends on rice husk biomass as an environmentally friendly alternative fuel using a bibliometric approach. Data were collected from the Scopus database covering publications from 2020 to 2026 using relevant keywords related to rice husk biomass and renewable energy. The data were analyzed using VOSviewer and Microsoft Excel to identify publication growth, dominant journals, collaboration networks, and keyword trends. The results show a significant increase in publications, reaching a peak in 2024, with Renewable Energy as the leading publication source. Keyword co-occurrence analysis revealed major themes such as biofuels, pyrolysis, combustion, and emission control. Thematic mapping indicates that combustion efficiency and thermal performance remain core research topics, while pelletizing and environmental assessment are emerging themes. This study provides insights into research directions and highlights the importance of technological innovation, efficiency improvement, and sustainability assessment to enhance rice husk utilization as a renewable energy source.